Urban Development in Conflict Zones: The Case of Gaza City - Palestine - Abukashif, Yousef J. M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Urban development is known as the system of residential expansion that expresses the image of any city. Consequently, the development of any area is done only by careful design that takes into account certain criteria that correspond to any region. Residential areas are the most important foundations of urban development, followed by other fields that support the development of any area which are very significant such as industrial, commercial and agricultural development. Moreover, the process of urban development takes place in two ways; urban development towards new uninhabited areas, secondly urban development in the affected areas by conflicts which is considered the most difficult situation. Furthermore, there are two main types of conflicts; internal and external. Both types are classifying to certain types of conflicts which are political, economic, social and institutional. It can be argued, that especially today, many places are facing economic and social problems through conflicts which have a great impact on their urban development process. This thesis attempts to understand and analyze urban development in conflict zones and reaching to solutions that will help to ensure urban development of these areas. The thesis focuses on Gaza city and its development process throughout conflict for the last two centuries as Gaza city contains a unique type of conflict. The thesis aims to analyze several aspects of urban development in the city such as residential, commercial, industrial and agricultural development. This marks an attempt to deal with the urban development situation in the city despite the conflict that is taking place in the intended case study. Mixed-methodological research approaches were used to collect information through qualitative literature review and quantitative observation of Gaza City including aerial maps, thermal maps and GIS maps analysis. The results obtained from the quantitative and qualitative methodologies have shown that urban development in Gaza City has over gone significant changes throughout the period of conflict. Finally, the thesis ends up with post- conflict proposals that could be beneficial to find solutions to urban development in Gaza city. In addition, this research aims to set forth some guidelines for "Urban Development in Conflict Zones" with emphasis on Gaza which could be adaptable for other cities/zones in conflict situation. Keywords: Urban development, Conflict zones, Land Use, GIS, Gaza city.

ÖZ: Kentsel gelişim, yerleşim alanlarının genişletilmesi ve aynı zamanda şehrin imajını ifade eden düzen olarak tanımlanabilir. Bu bağlamda, bir bölgenin gelişimi bu bölgenin belirli özgün kriterlerini dikkate alarak tasarlanması gerekmektedir. Konut yerleşim alanları, kentsel gelişimin en önemli temelleri olup, bunun yanında endüstriyel, ticari ve tarımsal alanlarda kentlerin gelişimini destekleyen diğer önemli alanlardır. Kentsel gelişme süreci genelde iki şekilde gerçekleşebilir; birincisi kentin doğal büyümesi ve yeni alanlara doğru gelişmesi; ikincisi, olası çatışmalardan etkilenen bölgelerdeki kentsel gelişme. Bu bağlamda, kentlerde genelde iki ana çatışma türü gözlemlenir: dış ve iç çatışma. Kentlerle ilişkin çatışmalar belirli çatışma türlerine göre sınıflandırılmaktadır: politik, ekonomik, sosyal ve kurumsal olarak tanımlanır. Özellikle günümüzde, dünyada birçok bölgenin çatışma bölgesi olduğundan dolayı, büyük ekonomik ve sosyal sorunlarla karşı karsıya kalarak, kentsel gelişim süreci ile ilgili ciddi sıkıntılar yaşanmaktadır. Bu tez, çatışma bölgelerindeki kentsel gelişmeyi anlamak ve analiz etmeği hedeflemektedir. Bu bağlamda, tezin hedefi, olası çatışmalardan etkilenen bölgelerde kentsel gelişimini sağlamaya yardımcı olacak çözümler önermektir. Bu araştırmada, vaka çalışması olarak, çatışma bölgesi olan Gazze Şehri ve bu kentin son yirmi yıllık kentsel gelişimini incelenmiştir. Tez, kentsel gelişimin analizini ve değerlendirmesini, bölgedeki konut, ticari, endüstriyel ve tarımsal alanların değişimini inceleyerek analiz etmeyi amaçlamaktadır. Bu bağlamda bu araştırma, vaka çalışmasında yer alan bölgesel çatışmaya rağmen, şehirdeki kentsel gelişimin devam ettiğini ve nasıl devam ettiğini vurgulamayı hedeflemektir. Bu çalışmada, niteleyici literatür taraması ve Gazze Şehri'nin hava, termal ve GIS haritaları analizi de dahil olmak üzere nicel gözlem yoluyla bilgi toplamak için karma yöntemsel araştırma yaklaşımları kullanılmıştır. Nicel ve nitel metodolojilerden elde edilen sonuçlar, Gazze Şehri'ndeki kentsel gelişimin, çatışma dönemi boyunca önemli değişimlere uğradığını göstermiştir. Son olarak, tez, Gazze kentinde kentsel gelişime çözüm bulmak için faydalı olabilecek çatışma sonrası önerilerle sonuçlanmaktadır. Buna ek olarak, bu araştırma, benzer durumda olan diğer şehirler / bölgeler için uyarlanabilen, Gazze’ye vurgu yaparak, “Çatışma Bölgelerinde Kentsel Gelişim” için bazı ilkeleri ortaya koymayı amaçlamaktadır. Anahtar Kelimer: Kentsel Gelişme, Çatışma bölgeleri, Arazi Kullanımı, GIS, Gazze Şehri
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assist. Prof. Dr. Müge Riza.
Keywords: Architecture; Urban Design; Urban Planning--City planning--Urban Development--Gaza City (Palestine); Planning--Environmental policy--Gaza City (Palestine); Urban development; Conflict zones; Land Use; GIS; Gaza city